Chromosome Evolution in the Family Solanaceae - Deanna, Rocío; Acosta, María Cristina; Scaldaferro, Marisel; Chiarini, Franco (Frontiers in Plant Science, 2022)
This review summarizes and discusses the knowledge of cytogenetics in Solanaceae, the tomato family, its current applications, and future prospects for making progress in fundamental systematic botany and plant evolution. We compile information on basic chromosome features (number, size, morphology) and molecular cytogenetics (chromosome banding and rDNA patterns). These data were mapped onto the Solanaceae family tree to better visualize the changes in chromosome features and evaluate them in a phylogenetic context. We conclude that chromosomal features are important in understanding the evolution of the family, especially in delimiting clades, and therefore it is necessary to continue producing this type of data. The potential for future applications in plant biology is outlined. Finally, we provide insights into understanding the mechanisms underlying Solanaceae’s diversification that could substantially contribute to developing new approaches for future research.